Self-Employment and its Relationship to Subjective Well-Being - Kara, Aycan; Petrescu, Maria (Senate Hall, 2018)
The subjective well-being of self-employed people has not received adequate attention. Our analysis focuses on how individuals' universal needs for autonomy, competence, and relatedness affect the happiness of self-employed persons, including whether there are significant differences among solo self-employed and those with employees. We use Self-Determination Theory and Hofstede's culture theory to address this gap. We study the relationship between autonomy, competence, relatedness and subjective well-being of self-employed people as well as the moderating effects of national cultural dimensions. We examine these hypothesized relationships using Hierarchical Linear Modelling across 4,856 self-employed individuals in 27 countries. Our results indicate that autonomy, competence, and relatedness are positively associated with the subjective well-being of self-employed individuals. Individualism moderates the relationship between autonomy and subjective well-being negatively and Uncertainty Avoidance moderates the relationship between relatedness and subjective well-being negatively. The findings represent a step forward in entrepreneurship research by examining the well-being of self-employed individuals. The study also provides information policymakers can utilize to encourage entrepreneurship using well-being as a motivational tool. Nevertheless, entrepreneurs can use these findings in formulating their long-term plans and business structure, as well as in motivating their employees. Keywords: self-employment, subjective well-being, Self-Determination Theory (STD), national culture, Hofstede
Keywords: self-employment|subjective well-being|Self-Determination Theory (SDT)|national culture|Hofstede